Investigation of O-Band Brillouin Fiber Laser Flatness at Different SOA Location - H. Ahmad; S. F. Norizan; M.Z. Zulkifli; C. H. Pua; Z.A. Ghani; S. W. Harun (Jurnal Fisika dan Aplikasinya, 2011)
In this paper, we present the different amplitude flatness of O-band Brillouin fiber laser resulting from placing the O band semiconductor optical amplifier at different locations. Stable and flatter peaks of multiwavelength Brillouin were generated by placing the SOA after the nonlinear medium instead of placing it before the nonlinear medium. The maximum number of Stokes are also differs between both configuration where the maximumnumber of stokes achieved was 12 generated by 1320 nm Brillouin pump with spacing channels of 12.72 GHz.